Reinventing the Peabody sisters - Elbert, Monika M. (Monika Maria), 1956-; Hall, Julie E. (Julie Elizabeth), 1957-; Rodier, Katharine (University of Iowa Press, 2006)
Whether in the public realm as political activists, artists, teachers, biographers, editors, and writers or in the more traditional role of domestic, nurturing women, Elizabeth Peabody, Mary Peabody Mann, and Sophia Peabody Hawthorne subverted rigid nineteenth-century definitions of women's limited realm of influence. Reinventing the Peabody Sisters seeks to redefine this dynamic trio's relationship to the literary and political movements of the mid nineteenth century. Previous scholarship has romanticized, vilified, or altogether erased their influences and literary productions or viewed the.